Citizen participation in natural protected areas governance in Andalucia: the case of the Natural Park Bay of Cadiz - Barragán Muñoz, Juan Manuel; Chica Ruiz, Juan Adolfo (Geographicalia, 2015)
Although nowadays the protected areas paradigm tends to a model in which citizens are able to participate actively in decision-making process, there are few empirical studies which corroborate such trends. That is why in this paper public participation is analyzed in a concrete area: the Bay of Cadiz Natural Park. To do so, quantitative and qualitative methodology is applied, based on the exploitation of a questionnaire exclusively designed for the Board members of this protected area, along with the scrutiny of different institutional public documents (meeting minutes, regulations, reports, etc.). This research allows a critical examination of different aspects affecting the internal governance of the protected area, as well as of the general framework in which this particular case occurs (Andalucia), which can be equally relevant within the national ambit. Final recommendations are aimed to seek improvement in standards for the governance of our natural capital.